Determination of Antiviral Drugs and Their Metabolites Using Micro-Solid Phase Extraction and UHPLC-MS/MS in Reversed-Phase and Hydrophilic Interaction Chromatography Modes - Fical, Luboš; Khalikova, Maria; Kočová Vlčková, Hana; Lhotská, Ivona; Hadysová, Zuzana; Vokřál, Ivan; Červený, Lukáš; Švec, František; Nováková, Lucie (Molecules (Basel, Switzerland), 2021)
Two new ultra-high performance liquid chromatography (UHPLC) methods for analyzing 21 selected antivirals and their metabolites were optimized, including sample preparation step, LC separation conditions, and tandem mass spectrometry detection. Micro-solid phase extraction in pipette tips was used to extract antivirals from the biological material of Hanks balanced salt medium of pH 7.4 and 6.5. These media were used in experiments to evaluate the membrane transport of antiviral drugs. Challenging diversity of physicochemical properties was overcome using combined sorbent composed of C18 and ion exchange moiety, which finally allowed to cover the whole range of tested antivirals. For separation, reversed-phase (RP) chromatography and hydrophilic interaction liquid chromatography (HILIC), were optimized using extensive screening of stationary and mobile phase combinations. Optimized RP-UHPLC separation was carried out using BEH Shield RP18 stationary phase and gradient elution with 25 mmol/L formic acid in acetonitrile and in water. HILIC separation was accomplished with a Cortecs HILIC column and gradient elution with 25 mmol/L ammonium formate pH 3 and acetonitrile. Tandem mass spectrometry (MS/MS) conditions were optimized in both chromatographic modes, but obtained results revealed only a little difference in parameters of capillary voltage and cone voltage. While RP-UHPLC-MS/MS exhibited superior separation selectivity, HILIC-UHPLC-MS/MS has shown substantially higher sensitivity of two orders of magnitude for many compounds. Method validation results indicated that HILIC mode was more suitable for multianalyte methods. Despite better separation selectivity achieved in RP-UHPLC-MS/MS, the matrix effects were noticed while using both chromatographic modes leading to signal enhancement in RP and signal suppression in HILIC.
Keywords: Antiviral Agents; hydrophilic interaction chromatography; antiviral drug; mikroextrakce na pevné fázi; Chromatography, Reverse-Phase; antivirové látky; Tandem Mass Spectrometry; monitorování léčiv; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; lidé; chromatografie s reverzní fází; reversed phase; reprodukovatelnost výsledků; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; Drug Monitoring; Solid Phase Microextraction; solid phase extraction; UHPLC-MS/MS; microextraction; Humans